بناء السرد القصصي في القصة الجزائرية قصة "المذنب" لياسمين بعطوش نموذجا - هيفاء ذويب; هناء دحة; نجلاء خلايفة; إزدهار دادة (جامعة الوادي - University of Eloued, 2025)
تناولنا في هذه المذكرة دراسة عنصر بناء السرد القصصي في القصة القصيرة قضة المذنب لياسمين بعطوش تطرقنا فيها إلى فصلين الفصل الأول تضمن القصة القصيرة ونشأتها حيث تعتبر فن أدبي حديثا ونشأة فيها صورتين شكليتين والفصل الثاني تضمن معطيات النظرية لعناصر السرد لقصة المذنب الإبراز تقنيات السرد وأساليبها. In this memorandum, we examine the narrative structure in Yasmine Batouche's short story "The Case of the Sinner." We discuss it in two chapters. The first chapter discusses the short story and its origins, as it is considered a modern literary art form and has two formal forms. The second chapter covers theoretical data on the narrative elements of "The Sinner," highlighting narrative techniques and styles.
مذكرة ليسانس. اللغة والأدب العربي . 2025.
Keywords: القصة القصيرة، السرد الحكي، السرد السريع، الرؤية السردية; short story; narrative narrative; rapid narration; narrative vision